If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + -1(-5) = -10 Multiply -1 * -5 A + 5 = -10 Reorder the terms: 5 + A = -10 Solving 5 + A = -10 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + A = -10 + -5 Combine like terms: 5 + -5 = 0 0 + A = -10 + -5 A = -10 + -5 Combine like terms: -10 + -5 = -15 A = -15 Simplifying A = -15
| 15x+10-2x-12=5 | | 2y+11=27 | | x^3-7x^2+3x-21= | | -8x-2y=-4 | | 4z+5-z= | | (2x-5)+52=(5x-15) | | 7y+3(y-5)=3(y+2)-2 | | r-25=-43 | | (2x-5)+52=5x-15 | | 4n-14=-6 | | -3(6+8m)=12-9(3m+5) | | -3[s]=18 | | 6x-15+3x=7+9x-22 | | 4x+2x=15+7x | | 1260=180(n-2) | | -6n=-30 | | -9(x-8)+(17x)=8(x-3)-17 | | 8x+9y=22 | | 4b-4(1-6)=b-9 | | 12-(x+6)=7x-2 | | 3x-4=2x+12 | | 4(7x+5)= | | 3x/5+2=x | | -9+(-9)= | | Y+(-8)=6 | | 3(x-1)+45=-3x | | 9y-13-4y+9=0 | | -2(k+4)=60 | | 7j=5j+10 | | X-(-4)=-9 | | 7+11j-2j=52 | | 11/131/2= |